Rational Actions of Widows Post Earthquake Disaster in Palu City - Ahsan, Sitti Chaeriah; Anriani, Haslinda B.; Nutfa, Moh.; Nugroho, Krisdaryadi Ponco; Sidin, Nurul Chudawiah; Akbar, Akbar (Devotion : Journal of Research and Community Service, 2023)
Earthquakes not only affect material losses, but also affect the socioeconomic lives of widowed women forcing them to act rationally to survive and avoid the threat of poverty. The study aims to analyze the impact of earthquake natural disasters with rational actions of widowed women after the earthquake disaster in Palu City. The research method uses a qualitative descriptive approach. Data collection was carried out through limited observation, in-depth interviews, FGDs and document studies so as to obtain primary and secondary data. Informants were purposively selected as many as 6 people. The data is analyzed interpretively. The validity of the data is done through triangulation. The results showed that in the face of poor post-disaster socioeconomic conditions, there are five models of strategies or rational survival actions carried out by widowed women, namely, borrowing business capital, building an entrepreneurial career, finding a new job, becoming a daily freelancer, and getting married. The forms of rational action carried out by widows are instrumental rational actions, value rationality actions and effective rational actions. It suggested the importance of socio-economic empowerment of widowed women appropriately and sustainably.